Google Earth forensics using Google Earth geo-location in digital forensic investigations - Harrington, Michael; Cross, Michael 1965- (Syngress, 2015)
This book explains how to use Google Earth in digital forensic investigations. This book teaches you how to leverage Google's free tool to craft compelling location-based evidence for use in investigations and in the courtroom. It shows how to e.
Includes index. - Includes bibliographical references and index. - Description based on print version record
Keywords: Criminal investigation -- Handbooks, manuals, etc; Forensic sciences -- Handbooks, manuals, etc; Evidence, Criminal -- Handbooks, manuals, etc; Forensic sciences; Enquêtes criminelles; Guides, manuels, etc; Criminalistique; Guides, manuels, etc; Preuve (Droit pénal); Guides, manuels, etc; Systèmes d'information géographique; Criminalistique; geographic information systems; forensic science; Criminal investigation; Evidence, Criminal; Handbooks and manuals